2002
DOI: 10.1200/jco.2002.11.151
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Anti–Gastrin-17 Antibodies, Raised to G17DT, in Advanced Pancreatic Cancer

Abstract: Patients with advanced pancreatic cancer are able to mount an adequate antibody response to G17DT. The 250- micro g dose is superior to the 100- micro g dose, and it appears to be generally well tolerated. Antibody responders demonstrate significantly greater survival than antibody nonresponders. Phase III studies are currently underway in order to determine efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Early human studies of G17DT in patients with other forms of cancer demonstrated that G17DT was safe and well tolerated [58]. In a phase II study of G17DT in advanced pancreatic cancer, 67% of 30 patients produced an antibody response [59]. The 250-g dose resulted in a significantly greater antibody response rate of 82%, compared with 46% for the 100-g group (p ϭ .018).…”
Section: Immunotherapy: Gemcitabine Plus Gastrin Vaccinementioning
confidence: 99%
“…Early human studies of G17DT in patients with other forms of cancer demonstrated that G17DT was safe and well tolerated [58]. In a phase II study of G17DT in advanced pancreatic cancer, 67% of 30 patients produced an antibody response [59]. The 250-g dose resulted in a significantly greater antibody response rate of 82%, compared with 46% for the 100-g group (p ϭ .018).…”
Section: Immunotherapy: Gemcitabine Plus Gastrin Vaccinementioning
confidence: 99%
“…These antigastrin antibodies can inhibit the proliferation of pancreatic cancer cells. In a phase II study of 30 patients with pancreatic cancer, 67% of patients were shown to mount an immune response to the vaccine [89]. Eighty-two percent of patients given the highest dose of the vaccine (250 µg) achieved a response.…”
Section: G17dtmentioning
confidence: 99%
“…G17DT (Gastrimmune™; Aphton Corp.; Miami, FL) is an immunoconjugate of the amino-terminal sequence of gastrin-17 (G-17) linked by means of a spacer peptide to diphtheria toxoid. Given as an intramuscular vaccination, it has been shown to induce the formation of antibodies that can neutralize endogenous G-17 and precursor glycine-extended G-17 [89]. These antigastrin antibodies can inhibit the proliferation of pancreatic cancer cells.…”
Section: G17dtmentioning
confidence: 99%
“…Gastrin is expressed early in the development of gastrointestinal carcinomas (6,7), and it is being tested as a therapeutic target in pancreatic, gastric, and colorectal cancer (6,8,9). An anti-gastrin vaccine is currently in phase III clinical trials (9) for pancreatic cancer.…”
mentioning
confidence: 99%